Postoperative Coronary Artery Bypass Graft Hospital Readmissions in Rural, Remote and Northern Communities: A Retrospective Case-Control Study - Alaeddine, Mariam (Université d'Ottawa / University of Ottawa, 2024)
Rural, remote, and northern communities (RRNC) have high rates of hospital readmissions post-coronary artery bypass graft (CABG). I performed a case-control study to understand the contributing factors associated with postoperative CABG readmissions in residents of RRNC, including the influence of the social determinants of health (SDOH). All patients readmitted within 30-days of CABG between 2021 and 2023 and a subset of non-readmitted patients, matched for age and sex, were included. Logistic regression showed that readmission was associated with myocardial infarction (OR 2.517; CI 1.493-4.242), surgical wait time (OR 1.016; CI 1.003-1.030), town of residence (OR 0.183; CI 0.066-0.512), distance from hospital (OR 1.010, CI 1.005 - 1.015), and need for community care (OR 14.968; CI 4.026-55.645). Factors for readmission were less associated with patient health factors but rather associated with SDOH, including, health services, physical environment, and community factors. Nursing implications include clinical practice, education, research, and health policy.
Keywords: Rural, remote, and northern communities; Social determinants of health; Coronary artery bypass graft; Post-operative readmissions